2017
DOI: 10.1371/journal.pone.0181886
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1-neutralizing antibody induced by simian adenovirus- and poxvirus MVA-vectored BG505 native-like envelope trimers

Abstract: Rabbits and monkeys immunized with HIV type 1 (HIV-1) native-like BG505 SOSIP.664 (BG505s) glycoprotein trimers are known to induce antibodies that can neutralize the autologous tier-2 virus. Here, we assessed the induction of HIV-1 trimer binding and neutralizing antibody (nAb) titres when BG505s trimers were also delivered by non-replicating simian (chimpanzee) adenovirus and non-replicating poxvirus modified vaccinia virus Ankara (MVA) vaccine vectors. First, we showed that approximately two-thirds and one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 62 publications
1
29
2
1
Order By: Relevance
“…These antibody titres also declined faster after immunization for the protein-only group. However, the homologous protein regimen induced more robust Tier 2 NAb titres than the ones that included ChAdOx1 and MVA [269].…”
Section: Viral-vectored Vaccinesmentioning
confidence: 90%
See 1 more Smart Citation
“…These antibody titres also declined faster after immunization for the protein-only group. However, the homologous protein regimen induced more robust Tier 2 NAb titres than the ones that included ChAdOx1 and MVA [269].…”
Section: Viral-vectored Vaccinesmentioning
confidence: 90%
“…Nonetheless, heterologous combinations of chimpanzee adenovirus Oxford 1 (ChAdOx1) [264] and modified vaccinia Ankara (MVA) [265] viral vectors have shown a good safety and immunogenicity profile [266][267][268]. Capucci et al showed that a sequential regimen of ChAdOx1, MVA and soluble BG505 SOSIP trimer protein induced similar binding-antibody titres to the protein-only regimen, while only the sequential regimen induced cytotoxic T cell responses [269]. These antibody titres also declined faster after immunization for the protein-only group.…”
Section: Viral-vectored Vaccinesmentioning
confidence: 99%
“…Reagents. BG505 SOSIP.664 trimers were expressed in CHO cells and purified as described previously (2). Rabbit MAbs 11A, 11B, and 12A were transiently expressed, affinity purified, and checked for purity and integrity as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…on the native HIV-1 trimer (1). Toward that end, the BG505 SOSIP.664 envelope (Env) glycoprotein trimer has been used in multiple animal immunization studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The BG505 Env glycoprotein lacks N-glycosylation sites at positions 241 and 289 (7,8).…”
mentioning
confidence: 99%
“…While these constructs have clearly solidified our knowledge of the challenges faced in HIV vaccine design, they have provided no clear path forward. Indeed, the focus on obtaining tier 2 virus neutralization may be detrimental, as this draws resources and focus from DNA and virus vectored regimens that, while not able to yield the same consistency in autologous tier 2 neutralization, can provide broader binding antibody responses [ 45 ]. Currently, the only inducible mechanism of protection we know of with some certainty is that protection against HIV acquisition can be elicited by broadly cross-reacting antibodies [ 46 ].…”
Section: Adenovirus Vectored Vlvs Targeting Hiv Siv and mentioning
confidence: 99%